ASSESSMENT OF MICHAEL PORTER'S COMPETITIVE STRATEGIES INFLUENCE ON FINANCIAL PERFORMANCE OF SMALLHOLDER TEA FACTORIES: A CASE OF KIAMBU AND MURANG'A COUNTIES - KIPKOSGEY, ROTICH DOMINIC; SANGORO, MR. OSCAR; OIRERE, Dr. DORCAS; ROMAN, MR. AKETCH (IJRDO - Journal of Business Management, 2016)
The main purpose of this study was to assess Michael Porter’s competitive strategies influenceon financial performance of smallholder tea factories in Kenya which has since been liberalisedunder the category of smallholder tea sub sector in Kenya. The study design used is a descriptiveresearch design to conduct the study, and the study area was Kiambu and Murang'a counties. Thetarget population of the study were tea farmers, tea factory employees and tea factory managersof the study area. The sample studied comprised of twelve smallholder tea factory companies inthe tea subsector spread over Kiambu and Murang'a counties in Kenya. The instrumentation usedwere questionnaires administered to respondents through emails and interview schedules whichwere used to sought more relevant information and clarify queries in the questionnaire. Theresearch study used both primary and secondary data from sampled respondents. Data wasanalysed by using of SPSS package version 17, where descriptive and regression model was usedto assess the relationship between the variables in the research study.From the findings it wasconcluded that Cost leadership strategy plays a significant role in determining the financialperformance of the smallholder tea factories in Kenya with a beta coefficient of 0.604, the effectis very significant at (p=0.000). Differentiation strategy is useful in making smallholder teafactories’s product stand-out against competitor’s products in the market.